IMPROVING STUDENT’S WRITING ABILITY THROUGH THE TASK-BASED LEARNING WORKSHEETS MODEL - Putri, Rini (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2025)
The four language skills that must be mastered by students include listening skills, speaking skills, reading skills, and writing skills. Among the four skills, writing skills are the least possessed by students. This can be seen from the value of the assignments given to students. This value does not meet the minimum completeness requirement of 75. Students only complete sober assignments without want to try as much as possible. This problem was also confirmed by the results of the interviews, which stated difficulties and confusion in understanding the assignments given, and even students had difficulty expressing ideas in written form. The purpose of this research is to improve students' writing skills through the application of task-based learning worksheets model. The research method is classroom action research. The sample used was 25 students, and the data collection technique used was observation and testing. The increase in writing ability occurred in cycle III. The results in cycle III for each indicator were good, as shown as follows: the composition achievement indicators obtained a value of 94%; cohesion and cohesion obtained a value of 98%; style and form of language obtained a value of 93%; mechanics and punctuation obtained a value of 95%; grammar and spelling obtained a value of 90%; and neatness of writing obtained a value of 90%.